Prinsip Dasar Restorative Justice dalam Menyelesaikan Perkara Pidana Anak - Nur, Muhammad Azhar; Jafar, Usman; Marilang, Marilang; Shuhufi, Muhammad (Jurnal Diskursus Islam, 2024)
The central issue of this study was the concept of restorative justice for children in confrontation with the law from an Islamic legal standpoint. This was a qualitative study employing a normative (syar'i) methodology. This study utilized primary data sources, including information from the Police, Prosecutors, Judges, and Social Institutions. And secondary sources such as books, journals, and articles. This study utilized observation, interviews, documentation, and reference tracking to acquire its data. Data processing and analysis procedures were implemented in a series of processes, including data selection, data examination, data classification, and data compilation. Based on the findings of this study, the fundamental elements of restorative justice in resolving criminal cases involving children in confrontation with the law are child protection, the best interests of the child, and kinship. In criminal cases involving children in dispute with the law, the concepts of restorative justice were implemented through mediation, deliberation, consensus, direction, and supervision of children. In criminal cases involving children in dispute with the law, the practice of restorative justice has the social effects of eradicating the stigma or labeling of children as mischievous, as well as promoting child growth and child development.